2020
DOI: 10.1002/jum.15413
|View full text |Cite
|
Sign up to set email alerts
|

Are Convolutional Neural Networks Trained on ImageNet Images Wearing Rose‐Colored Glasses?: A Quantitative Comparison of ImageNet, Computed Tomographic, Magnetic Resonance, Chest X‐Ray, and Point‐of‐Care Ultrasound Images for Quality

Abstract: Objectives Deep learning for medical imaging analysis uses convolutional neural networks pretrained on ImageNet (Stanford Vision Lab, Stanford, CA). Little is known about how such color‐ and scene‐rich standard training images compare quantitatively to medical images. We sought to quantitatively compare ImageNet images to point‐of‐care ultrasound (POCUS), computed tomographic (CT), magnetic resonance (MR), and chest x‐ray (CXR) images. Methods Using a quantitative image quality assessment technique (Blind/Refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Spatial and temporal resolution and deep learning algorithms have demonstrated variable effects in early studies, having the potential for greater or lesser sensitivity, and are likely bounded by the subjective image search and acquisition process. [45][46][47] Nonetheless, this study has demonstrated that a specific ultrasound examination can be performed during telehealth by patients without any prior training and has future implications for this methodology in other disease states. In COVID-19, the simplified lung examination could be performed not only from home isolation by patients but also in emergency departments, urgent care facilities, or COVID-19 testing centers for outpatients with minimal symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…Spatial and temporal resolution and deep learning algorithms have demonstrated variable effects in early studies, having the potential for greater or lesser sensitivity, and are likely bounded by the subjective image search and acquisition process. [45][46][47] Nonetheless, this study has demonstrated that a specific ultrasound examination can be performed during telehealth by patients without any prior training and has future implications for this methodology in other disease states. In COVID-19, the simplified lung examination could be performed not only from home isolation by patients but also in emergency departments, urgent care facilities, or COVID-19 testing centers for outpatients with minimal symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…Large image databases such as Imagenet 12 permit initial weights preadjustment in order to make borders or other basic features of images more easily recognizable by algorithms 20 . However, in the case of ultrasound, some authors suggest that initial weight adjustments should be made with the same kind of images to improve system accuracy 21 . This is a controversy, which could foster the necessity of creating largely public ultrasound images databases.…”
Section: Discussionmentioning
confidence: 99%
“…For algorithm creation, researchers used an Anaconda package manager with Python programming language version 3.72, to facilitate scripting and package management. Based on superior performance in prior studies, we decided upon a publicly available Keras‐based (a python deep learning framework or library) VGG‐16 bidirectional LSTM ML algorithm 18 . VGG‐16 model architecture is accessible from multiple public sources including an online repository, http://github.com.…”
Section: Methodsmentioning
confidence: 99%
“…Based on superior performance in prior studies, we decided upon a publicly available Kerasbased (a python deep learning framework or library) VGG-16 bidirectional LSTM ML algorithm. 18 VGG-16 model architecture is accessible from multiple public sources including an online repository, github.com. The VGG convolutional neural network (CNN) is an early CNN version and contains 16 layers, while most recent CNNs have hundreds of layers.…”
Section: Algorithm Designmentioning
confidence: 99%